2015
DOI: 10.1111/jdi.12350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromium malate on glycometabolism, glycometabolism‐related enzyme levels and lipid metabolism in type 2 diabetic rats: A dose–response and curative effects study

Abstract: Aims/IntroductionThe present study was designed to evaluate the effect of chromium malate on glycometabolism, glycometabolism-related enzyme levels and lipid metabolism in type 2 diabetic rats, and dose–response and curative effects.Materials and MethodsThe model of type 2 diabetes rats was developed, and daily treatment with chromium malate was given for 4 weeks. A rat enzyme-linked immunosorbent assay kit was used to assay glycometabolism, glycometabolism-related enzyme levels and lipid metabolism changes.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Previous studies revealed the key role of chromium as a blood glucose and lipid regulator [17,18]. Both in a diabetic rodent model and patients, chromium supplementation could improve glucose and lipid metabolism [11,19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed the key role of chromium as a blood glucose and lipid regulator [17,18]. Both in a diabetic rodent model and patients, chromium supplementation could improve glucose and lipid metabolism [11,19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…[10]. Chromium can reduce fasting blood glucose levels in diabetic patients and diabetic rodent models [11], and enhance insulin action, including activation of insulin receptor sites [12]. Diabetic animals [13] and patients [14,15] have lower chromium levels than that of controls.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that trace elements, especially chromium (Cr), play a significant role in the metabolism of lipids and carbohydrates (Feng et al, 2015). Chromium as a cofactor of chromodulin, a low molecular weight oligopeptide, by attaching to the β-subunit of the insulin receptor and activating tyrosine kinase, increases the effect of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Chromium supplementation can significantly cut down total cholesterol (TC) and low-density lipoprotein (LDL) levels in Type 2 diabetes (T2D) subjects [710], women with polycystic ovary syndrome [11] and high fat diet rats [12,13]. The suggested minimum daily intake of chromium is 30 μg.…”
Section: Introductionmentioning
confidence: 99%